Novel Approaches for the Analysis and Isolation of Benzylisoquinoline Alkaloids in Chelidonium majus - Zwerger, Michael; Boeck, Lynda; Manzl, Julia; Schwaiger, Stefan; Ganzera, Markus (Planta Medica, 2024)
Benzylisoquinoline alkaloids are the major bioactive components in Chelidonium majus, a plant that has a long usage history for the treatment of gastrointestinal ailments in European and Asian phytomedicine. This study reports on the development and application of a supercritical fluid chromatography technique for the simultaneous qualitative and quantitative determination of seven benzylisoquinoline alkaloids in under six minutes using a Viridis BEH 2-EP column and a modifier comprising methanol with 30% acetonitrile and 20 mM ammonium formate. The method was fully validated according to ICH guidelines showing, e.g., excellent linearity (≥ 0.9997) and maximum deviations for intraday and inter-day precision of 2.99 and 2.76%, respectively. The new supercritical fluid chromatography assay was not only employed for the analysis of several C. majus samples but was also used for the subsequent development of a fast centrifugal partition chromatography technique, whereby five benzylisoquinoline alkaloids could be isolated within approximately 2.5 h, with only two of them, protopine and chelidonine, requiring an additional purification step. To achieve this, a solvent system composed of chloroform/methanol/0.3 M hydrochloric acid was used in descending mode. By injecting 500 mg of crude extract, stylopine (1.93 mg), sanguinarine (0.57 mg), chelidonine (1.29 mg), protopine (1.95 mg), and coptisine (7.13 mg) could be obtained. The purity of compounds was confirmed by supercritical fluid chromatography and MS.
Keywords: Chelidonium majus; Papaveraceae; supercritical fluid chromatography; UHPSFC; fast centrifugal partition chromatography; FCPC; benzylisoquinoline alkaloids